Positive Moderation in Islamic Education: A Sociological Analysis of Its Implementation in Muhammadiyah Schools - Dartim, Dartim; Ali, Mohamad Wahyu; Santoso, Tri; Azani, Moh. Zakki; Noor, Iqbal Hidayatsyah; Febriandika, Nur Rizqi (EDUKASIA, 2026)
The increasing prevalence of bullying in Indonesian educational institutions reflects deeper structural and cultural challenges within the education system. This study aims to analyze the implementation of positive moderation in Islamic education within Muhammadiyah schools as a preventive strategy against bullying. This research employed a qualitative field research design using a sociological approach to education. Data were collected through observation, interviews, focus group discussions (FGDs), and documentation, involving stakeholders in Muhammadiyah schools in Sragen Regency. Data analysis was conducted using the interactive model proposed by Matthew B. Miles and A. Michael Huberman, and was further strengthened by Pierre Bourdieu’s theory capital. The findings indicate that positive moderation is systematically implemented through curriculum integration, dialogical and participatory active learning, and the development of an inclusive school culture. Theoretically, this study contributes to the expansion of religious moderation into a broader framework of educational moderation. Practically, it offers a model for developing a humanistic and adaptive Islamic education system in response to contemporary social and interactive challenges.